BIOAKTIVITAS DAN KANDUNGAN GENUS Callicarpa - Erwin - (JURNAL KIMIA MULAWARMAN, 2016)
allicarpa L is one genus of the family Lamiaceae. Callicarpa consisting of approximately 150 species such as shrubs and trees. Various species of Callicarpa is widely used in traditional medicine and it was potentially as antinociceptive, antioxidant, antimicrobial and thrombolytic drugs. Based on various reports results of previous studies have found various types of secondary metabolites from plants Callicarpa such as terpenoids, steroids and flavonoids. Some of these compounds can be developed as an anti A. aegypti mosquito, Anopheles stephensi, and natural pesticides.